India’s Need for Higher Education Internationalization - Altbach, Philip G.; Mathews, Eldho (International Higher Education, 2015)
India, with the world’s second largest higher education system, has little international consciousness. This article argues that India needs an internationalization strategy, and points to some of the challenges in creating such a program.